New species of Desmiphorini (Coleoptera: Cerambycidae: Lamiinae) from the Reserva Biológica Alberto Manuel Brenes, Alajuela, San Ramón, Costa Rica - Galileo, M. H. M.; Esteban-Duran, J. R. (Spanish Journal of Agricultural Research, 2010)
A new species of the genus Esaguasu Galileo and Martins, 2007, Esaguasu brenensis sp. nov. is described from the unique specimen collected during 2007 in the Reserva Biológica Alberto Manuel Brenes, San Ramón, Alajuela, Costa Rica.